Bitopic fluorescent antagonists of the A2A adenosine receptor based on pyrazolo[4, 3-e][1, 2, 4]triazolo[1, 5-c]pyrimidin-5-amine functionalized congeners. Issue 8 (11th July 2017) - Duroux, Romain; Ciancetta, Antonella; Mannes, Philip; Yu, Jinha; Boyapati, Shireesha; Gizewski, Elizabeth; Yous, Said; Ciruela, Francisco; Auchampach, John A.; Gao, Zhan-Guo; Jacobson, Kenneth A.
Abstract : Functionalized antagonist probes of the A2A adenosine receptor. Abstract : A pyrazolo[4, 3- e ][1, 2, 4]triazolo[1, 5- c ]pyrimidin-5-amine antagonist of the A2A adenosine receptor (AR) was functionalized as amine congeners, fluorescent conjugates and a sulfonate, and the A2A AR binding modes were predicted computationally. The optimal n -butyl spacer was incorporated into the following A2A AR-selective ( K i, nM) conjugates: BODIPY630/650 derivative11 (MRS7396, 24.6) and AlexaFluor488 derivative12 (MRS7416, 30.3). Flow cytometry of12 in hA2A AR-expressing HEK-293 cells displayed saturable binding (low nonspecific) and inhibition by known A2A AR antagonists. Water-soluble sulfonate13 was a highly potent ( K i = 6.2 nM) and selective A2A AR antagonist based on binding and functional assays. Docking and molecular dynamics simulations predicted the regions of interaction of the distal portions of these chain-extended ligands with the A2A AR. The BODIPY630/650 fluorophore of11 was buried in a hydrophobic interhelical (TM1/TM7) region, while AlexaFluor488 of12 associated with the hydrophilic extracellular loops. In conclusion, we have identified novel high affinity antagonist probes for A2A AR drug discovery and characterization.